2007
DOI: 10.1136/adc.2007.120584
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ibuprofen and indometacin for early-targeted treatment of patent ductus arteriosus in extremely premature infants: a randomised controlled trial

Abstract: Ibuprofen is as effective as indometacin for the early-targeted PDA treatment in extremely premature infants, without increasing the incidence of complications. When the echocardiographic PDA flow pattern was used as a guide for PDA treatment, fewer doses of drugs were needed to achieve acceptable closing rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 37 publications
8
70
0
2
Order By: Relevance
“…Search results and citation lists for prior publications identified 75 randomized-controlled trials of interventions that close a PDA in preterm infants. In 26 trials (five comparing long and short courses of indomethacin, [37][38][39][40][41] 19 comparing indomethacin and ibuprofen, [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and two that included very early crossover to treatment of nonresponders 29,61 ), rates of ductal closure did not differ between treatment assignments, precluding evaluation of effects of ductal closure on other outcomes, so these were excluded. The remaining 49 trials, 36, including 4728 subjects, were deemed potentially informative, as all but one documented substantial reduction in ductal patency after treatment.…”
Section: Findings From Individual Randomized-controlled Trialsmentioning
confidence: 99%
“…Search results and citation lists for prior publications identified 75 randomized-controlled trials of interventions that close a PDA in preterm infants. In 26 trials (five comparing long and short courses of indomethacin, [37][38][39][40][41] 19 comparing indomethacin and ibuprofen, [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and two that included very early crossover to treatment of nonresponders 29,61 ), rates of ductal closure did not differ between treatment assignments, precluding evaluation of effects of ductal closure on other outcomes, so these were excluded. The remaining 49 trials, 36, including 4728 subjects, were deemed potentially informative, as all but one documented substantial reduction in ductal patency after treatment.…”
Section: Findings From Individual Randomized-controlled Trialsmentioning
confidence: 99%
“…Indomethacin, used since 1976, has been shown to be effective in producing closure of the ductus between 60 to 80% of patients, decreasing its effectiveness at younger gestational age 11,12 . In the last decade, similar results have been observed with the use of ibuprofen IV; both drugs have been shown to be equally effective in ductal closure and to reduce surgical ligation rates of PAD [13][14][15] . If closure of the PAD is not achieved with one or two cycles of NSAID therapy, surgical closure is indicated 16 .…”
Section: Introductionmentioning
confidence: 53%
“…In infants without SIP, 37/93 (39.8%) infants had a moderate or large PDA after the first course of ibuprofen, whereas in the remaining, 24/93 (25.8%) had clinical or ECHO (32, 34.4%) showed closure. Eight (8,8.3%) infants without SIP received a second course of ibuprofen and three (3.2%) infants received indomethacin for persistent PDA.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported using prophylactic intravenous ibuprofen within 6 to 8 h after birth, with bowel perforation occurring in 8.0 to 8.3% of the infants, 8,21 whereas another study reported bowel perforation in 8.0% when ibuprofen (treatment) was used at a median age of 6 days. 22 Bowel perforation has also been reported in isolated infants within 48 h of oral ibuprofen prophylaxis, or with treatment of PDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation